FENOMENA POPULATION AGEING: KAJIAN KUALITATIF PERGESERAN DEMOGRAFIS, AKAR PENYEBAB, DAN IMPLIKASINYA TERHADAP EKONOMI - Munzir Phonna; Enjelika Simamora; Eva Ulina Br Hombring; Rinaldi; Yan Septian; Yosua Simanjuntak (Adiba Aisha Amira, 2026)
This study examines the phenomenon of population ageing through a qualitative approach, focusing on three main dimensions: demographic structural shifts, root causes of ageing acceleration, and its economic implications. Findings show that the research location has officially entered the ageing society phase, marked by an increase in the proportion of elderly aged 60 years and above to 14.8% and an old-age dependency ratio rising to 13.2. Three interrelated factors drive this acceleration: a sharp decline in the Total Fertility Rate to 1.8, an increase in life expectancy to 74.1 years, and high out-migration of the productive age group at 34%. Economic implications include a decline in local economic growth from 6.2% to 4.1% per year, a decrease in labor force participation, with 67% of the elderly still working in the informal sector due to limited social protection. Fiscal pressure is evidenced by increased local budget allocation for elderly programs to 8.7%, and household expenditure dominated by elderly healthcare costs at 23%. Nevertheless, population ageing also opens new economic opportunities through the silver economy concept.